Pendidikan Karakter Dalam Tasawuf Modern Hamka Dan Tasawuf Transformatif Kontemporer - Supriyadi Supriyadi; Miftahol Jannah (Universitas Muhammadiyah Sidoarjo, 2019)
The concept of character education in Hamka's modern mysticism, including sincerity, fear, zuhud, and resignation. Sincerity requires the existence of siddiq and a sense of fear of fear that exists in humans, put only on God, namely fear because of the doom, torment and wrath of Allah. The character of zuhud is born as a manifestation of faith. Tawakkal is interpreted as a form of submission of decisions of every human endeavor and effort only to Allah SWT. Approach in character education, Hamka offers a trilogy of the concept of Sufism trilogy, namely takhalli, tahalli, and tajalli. Takhalli, is self-liberation from despicable qualities. Tahalli, is the stage of filling and decorating yourself with commendable attitudes. Tajalli is an appreciation of the divine sense or in Hamka's terms,